Economic Comparison of Wood and Fiberglass Fishing Vessels Produced in Traditional Yards - Rizwan, Thaib; Mahya, Dyti Nourra; Rizqi, Rahmat; Setiawan, Ichsan; El Rahimi, Sayyid Afdhal; Thaib, Razali; Arif, Muhammad (Transactions on Maritime Science, 2024)
Wooden boats are commonly considered to be more cost effective compared to fiberglass boats, and no study has described the economic disparities between the two vessel types. Therefore, this study aimed to provide a comprehensive economic comparison between wooden and fiberglass boats, including the return-on-investment timelines and the potential profitability. A qualitative method was used in this study, and the data were collected through survey techniques. The economic analysis results showed that the average Net Present Values of wooden and fiberglass boats were IDR 72,935,055 and IDR 84,511,500 respectively. The average Net Benefit-Cost Ratio and the average Internal Rate of Return for both vessel types were 1 and 11%. The average Payback Period was approximately 6.6 years for wooden boats with a profit of IDR 8,902,000, and 6 years for fiberglass boats with a profit of IDR 11,936,944. In conclusion, the use of both vessels was not only acceptable but feasible for operation.